Reforming the world : social activism and the problem of fiction in nineteenth-century America - Sánchez, María Carla, 1968- (University of Iowa Press, 2008)
Reforming the World considers the intricate relationship between social reform and spiritual elevation and the development of fiction in the antebellum United States. Arguing that novels of the era engaged with questions about the proper role of fiction taking place at the time, Maria Carla Sánchez illuminates the politically and socially motivated involvement of men and women in shaping ideas about the role of literature in debates about abolition, moral reform, temperance, and protest work. She concludes that, whereas American Puritans had viewed novels as risqué and grotesque, antebellum re.